1995
DOI: 10.1037/0003-066x.50.9.782
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exposure to violence on young children.

Abstract: Violence has been characterized as a "public health epidemic" in the United States. At the same time, children's witnessing of violence is frequently overlooked by law enforcement officers, families, and others at the time of a violent incident. Although mothers describe the panic and fear in their children and themselves when violence occurs, little research or clinical attention has focused on the potential impact on children of living under conditions of chronic community violence. The purpose of this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
220
3
12

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(242 citation statements)
references
References 26 publications
7
220
3
12
Order By: Relevance
“…Children in the high-stress neighborhood described more severe violence, but included fewer reports of own or others' emotions or mental states, and gave less explicit moral evaluations in their stories than did the children from the moderate-stress neighborhood. This is consistent with previous research that has suggested that exposure to neighborhood violence presents a significant threat to children's moral development (Farrell et al 2007;Osofsky 1995Osofsky , 1997.…”
Section: Examplesupporting
confidence: 93%
“…Children in the high-stress neighborhood described more severe violence, but included fewer reports of own or others' emotions or mental states, and gave less explicit moral evaluations in their stories than did the children from the moderate-stress neighborhood. This is consistent with previous research that has suggested that exposure to neighborhood violence presents a significant threat to children's moral development (Farrell et al 2007;Osofsky 1995Osofsky , 1997.…”
Section: Examplesupporting
confidence: 93%
“…Previous studies have suggested that exposure of young people to a violent environment can produce feelings of anger and irritability (Osofsky, 1995) with negative results on academic performance. Young people with problems of self-control find it difficult to negotiate on requests coming from the school.…”
Section: Discussionmentioning
confidence: 99%
“…For example, children who are characterized by impairments in emotion regulation or maladaptive biases in social information processing may be particularly likely to become involved in high-conflict dyadic peer relationships (Dodge, Price, Coie, and Christopoulos, 1990;Hubbard and others, 2001). These deficits could in turn interfere with children's ability to cope with community violence exposure and other urban stressors (Osofsky, 1995). From this perspective, children who frequently become involved in mutual antipathies with peers might be conceptualized as a vulnerable subgroup.…”
Section: Implications Of Our Findingsmentioning
confidence: 98%